5 YEARS OF ION-LASER INTERACTION MASS SPECTROMETRY—STATUS AND PROSPECTS OF ISOBAR SUPPRESSION IN AMS BY LASERS. Issue 3 (14th June 2022) - Martschini, Martin; Lachner, Johannes; Hain, Karin; Kern, Michael; Marchhart, Oscar; Pitters, Johanna; Priller, Alfred; Steier, Peter; Wiederin, Andreas; Wieser, Alexander; Golser, Robin
ABSTRACT: A setup for ion-laser interaction was coupled to the state-of-the-art AMS facility VERA five years ago and its potential and applicability as a new means of isobar suppression in accelerator mass spectrometry (AMS) has since been explored. Laser photodetachment and molecular dissociation processes of anions provide unprecedented isobar suppression factors of >10 10 for several established AMS isotopes like 36 Cl or 26 Al and give access to new AMS isotopes like 90 Sr, 135 Cs or 182 Hf at a 3-MV-tandem facility. Furthermore, Ion-Laser InterAction Mass Spectrometry has been proven to meet AMS requirements regarding reliability and robustness with a typical reproducibility of results of 3%. The benefits of the technique are in principle available to any AMS machine, irrespective of attainable ion beam energy. Since isobar suppression via this technique is so efficient, there often is no need for any additional element separation in the detection setup and selected nuclides may even become accessible without accelerator at all.